In vitro and in vivo evaluation of 2-aminoalkanol and 1,2-alkanediamine derivatives against Strongyloides venezuelensis (2016)
Background: Strongyloidiasis is a parasitic disease widely present in tropical and subtropical areas. Strongyloides stercoralis represents the main species that infects human beings. Ivermectin is the current drug of choice; however, issues related with treatment failure in patients with diabetes or infected with T-lymphotropic virus-1 make the identification of new molecules for alternative treatment a priority. In the present study, the activity of sphingosine-related aminoalcohol and diamine were evaluated against Strongyloides venezuelensis third-stage larva (L3) cultures and experimental infections in mice. Methods: The efficacy of each compound against L3 was assessed using both XTT (2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide) assay and microscopic observation with concentrations ranging from 1 to 350 µM. Cytotoxicity was evaluated using J774.2 macrophage cell line and XTT assay. Lethal concentration 50 (LC50), selectivity index (SI) and structure-activity relationships were established. The activity compounds 4 (2-(ethylamino) hexadecan-1-ol), 6 (2-(butylamino) hexadecan-1-ol), 17 (tert-butyl N-(1-aminododecan-2-yl) carbamate) and 18 (tert-butyl N-(1-aminohexadecan-2-yl) carbamate) were further assessed against experimental S. venezuelensis infections in CD1 mice measuring reductions in the numbers of parthenogenetic females and egg passed in faeces. Mice were infected with 3,000 L3 and treated with 20 mg/kg/day for five days. Results: In the screening study of 15 aminoalcohols [lauryl (n = 9); palmityl (n = 13); stearyl (n = 15) and alcohol derivatives], the presence of a palmitol chain was associated with the highest efficacy against L3 (LC50 31.9-39.1 µM). Alkylation of the 2-amino group with medium size fragments as ethyl or n-butyl showed the best larvicidal activity. The dialkylation did not improve efficacy. Aminoalcohols 4 and 6 showed the highest SI (1.5 and 1.6, respectively). With respect to diamine derivative compounds, a chain size of sixteen carbon atoms (palmitoyl chain, n = 13), and the alkylation of the 2-amino group with medium-sized fragments, were associated with the highest lethal activities. The presence of carbamoyl group in diamines 17 and 18 yielded high SI (1.7 and 1.4, respectively). Infected mice treated with aminoalcohol 6 showed reduction in parthenogenetic females (59 %) and eggs in faeces (51 %). Conclusions: These results support the potentiality of aminoalcohol and diamine sphingosine-related compounds as suitable prototypes for developing new promising drugs against strongyloidiasis. © 2016 The Author(s).